2019
DOI: 10.18488/journal.aefr.2019.97.789.806
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequality and its Implication for Inclusive Growth in Nigeria from 1980 to 2018

Abstract: Earlier empirical studies on inequality concentrated more on its effects on economic growth with limited attention on its consequences for inclusive growth. Nigeria on average has achieved its annual target growth rate. However, stark realities of inequality, unemployment and poverty amid growth point to the need for inclusive growth. This paper examined the gender inequality implications for inclusive growth in Nigeria from 1980 to 2018 using data from the World Development Indicators (2018), National Bureau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, factors such as infrastructure, labor force, TO, and inflation have impacted the economic progress of Asian nations. Olanrewaju, Tella, and Adesoye (2019) revealed that the interaction between IQ and financial inclusion and inclusive finance had a bidirectional causal link. This suggests that even while institutional quality may have a broad range of economic impacts, it seems to be the main engine of inclusive growth.…”
Section: Institutional Quality and Inclusive Growthmentioning
confidence: 99%
“…Furthermore, factors such as infrastructure, labor force, TO, and inflation have impacted the economic progress of Asian nations. Olanrewaju, Tella, and Adesoye (2019) revealed that the interaction between IQ and financial inclusion and inclusive finance had a bidirectional causal link. This suggests that even while institutional quality may have a broad range of economic impacts, it seems to be the main engine of inclusive growth.…”
Section: Institutional Quality and Inclusive Growthmentioning
confidence: 99%
“…Perbedaan tersebut menyebabkan perempuan menerima upah yang lebih rendah daripada laki-laki (Laili & Damayanti, 2018) Assoumou-ella (2019) menemukan bahwa semakin tinggi kesetaraan gender pada pendidikan berpengaruh positif secara signifikan terhadap (Produk Domestik Bruto) PDB per kapita. Bertay et al dalam Lawanson & Umar (2019) juga menganalisis pengaruh ketimpangan gender pada pendidikan dan pekerjaan. Hasilnya menunjukkan bahwa ketimpangan gender pada kedua indikator tersebut dapat menurunkan pertumbuhan ekonomi seiring dengan menurunnya pendapatan per kapita dan konsumsi per kapita akibat penurunan output.…”
Section: Pendahuluanunclassified
“…Schober & Winter-Ebmer (2011) juga membuktikan bahwa kesenjangan yang terjadi pada upah yang diberikan kepada pekerja perempuan dan laki-laki berdampak pada penurunan pertumbuhan ekonomi. Beberapa hasil penelitian tersebut didukung oleh penelitian yang dilakukan Lawanson & Umar (2019) yang membuktikan bahwa ketimpangan gender dalam pendidikan dan pekerjaan signifikan berpengaruh negatif terhadap pertumbuhan ekonomi inklusif.…”
Section: Pendahuluanunclassified
“…Results demonstrated a substantial relationship between the share of women's employment rate and the number of male education enrollments. In the same vein, Olukemi and Dominic (2019) investigated the impacts of gender disparity on inclusive growth in Nigeria. The results of the autoregressive distributed lag (ARDL) model using yearly data from 1980 to 2018 showed that gender inequality – particularly in education and employment – has grave effects on Nigeria's ability to attain steady‐state growth.…”
Section: Literature Reviewmentioning
confidence: 99%